Correlational study on cyberbullying and social abilities in intercultural teenagers - Tomé-Fernández, María; Ortiz-Marcos, José Manuel; Fernández-Leyva, Christian (Frontiers in Psychology, 2022)
This article analyzes the relationship between cyberbullying profile by racist reasons and social abilities of a group of intercultural teenagers living in Spain (N=1478). The study includes participants aged between 12 and 16 years old (M=13.99; SD=1.352). Of these, 738 were male (49.9%) and 740 female (50.1%). A correlational study was carried out applying two online tools with suitable psychometrics parameters (content-construct validity and reliability), the first one was a scale that measured social abilities and the second evaluated the racist or xenophobic cyberbullying differentiating the victim and aggressor profile. The results indicated five main findings: 1) generally, the participants analyzed present all the social abilities; (2) for the most part, these participants do not normally experience cyberbullying; (3) a positive correlation exists between the majority of social abilities analyzed and the cyber-victim profile. It was also observed a negative correlation between the social ability associated with the ability of making requests, and this profile; (4) there is a positive correlation among the six social abilities analyzed and the cyber-aggressor profile; (5) the racist or xenophobic cyberbullying are driven not only by the absence of social abilities, but in some cases they are also driven by socio-demographic variables (i.e. age and gender). Likewise, this work shows how the absence of some social abilities in some participants involve racist or xenophobic experiences as victims and as aggressors, which may be of interest for the analysis of teenagers behavior in intercultural contexts, as well as according to age and gender. More transcultural research would need to be carried out in order to know the global perspective of the link between social abilities and the different profiles of racist and xenophobic cyberbullying, framed in the context of social psychology and studies of mass communication.